Do sensation seeking and aggression traits moderate the association between peer influence and alcohol outcomes among young Swiss men?. (2nd January 2018) - Grazioli, Véronique S.; Gmel, Gerhard; Mohler-Kuo, Meichun; Daeppen, Jean-Bernard; Bertholet, Nicolas; Studer, Joseph
Abstract: Peer influence is a strong predictor of drinking behaviors, yet not all young adults respond to its influence in the same way. This study aimed to identify young adults who are more vulnerable to peer influence by prospectively examining whether sensation seeking and aggression traits moderate the associations between peer influence and alcohol use and related consequences among young male drinkers. Participants ( N  = 4, 624 participants) were young Swiss men from the Cohort Study on Substance Use Risk Factors. Measures of peer influence (i.e. descriptive norms and peer pressure to engage in misconduct), sensation seeking, aggression and alcohol use and related consequences were used from the baseline and 15-month follow-up assessments. Findings indicated that neither sensation seeking nor aggression significantly moderated the associations between peer influence and alcohol-related consequences. However, they revealed that sensation seeking and aggression had a moderating effect on the association between peer influence and total drinks per year, such that this association was overall stronger among participants scoring lower on personality traits. These findings suggest that young male drinkers with low scores on sensation seeking and aggression may benefit from stand-alone selective interventions targeting peer influence, whereas those scoring higher on these personality traits may rather benefit from programs that include interventions targeting both peer influence and personality risk factors of drinking behaviors.